Adaptive Management and Quail Conservation on Rangelands in the American West - Leonard A. Brennan; Ashley Tanner; Evan P Tanner (National Quail Symposium Proceedings, 2022)
Adaptive management has been and is being practiced with the goal of sustaining populations of wild quails on large areas of rangelands in the American West. Because the current land use practices throughout most of the eastern two-thirds of the United States largely do not promote early-successional vegetation communities, rangelands contain the largest remaining blocks of contiguous (unfragmented) habitat for the northern bobwhite (Colinus virginianus) and the other 5 species of quails found in the western states. Many wildlife professionals on both private and public rangelands are practicing a diverse array of quail habitat and population management actions that could be considered a form of adaptive management—an iterative process used to make decisions in the context of uncertainty. Though this “learning by doing” approach is not always formally labeled adaptive management, these wildlife professionals intuitively recognize the value of the process in sustaining populations of wild quails. We support our assertions about adaptive management with 4 case study examples of adaptive management projects that promote quail conservation—including quail hunting—on both private and public rangelands in the American West. By discussing these scenarios within an adaptive management framework, we hope to highlight current and future opportunities for adaptive management in quail conservation on rangelands and to discuss where adaptive management may be improved or no longer be appropriate.
Keywords: adaptive management; case studies; habitat management; harvest management; integration of technology joint ventures; restoration management